Intermittent Scanning Glucose Monitoring or Predicted Low Suspend Pump Treatment: Does It Impact Time in Glucose Target and Treatment Preference? The QUEST Randomized Crossover Study - Schierloh, Ulrike; Aguayo, Gloria A.; Schritz, Anna; Fichelle, Muriel; De Melo Dias, Cindy; Vaillant, Michel T.; Cohen, Ohad; Gies, Inge; de Beaufort, Carine (Frontiers in Endocrinology, 2022)
Objective To compare glycemic control and treatment preference in children with type 1 diabetes (T1D) using sensor augmented pump (SAP) with predictive low glucose suspend (SmartGuard®) or pump with independent intermittent scanning continuous glucose monitoring (iscCGM, Freestyle libre ®). Methods In this open label, cross-over study children, 6 to 14 years, treated with insulin pump for at least 6 months were randomized to insulin pump and iscCGM (A) or SAP with SmartGuard® (B), for 5 weeks followed by 5 other weeks. The difference in percentages of time in glucose target (TIT), (3.9 – 8.0 mmol/l), <3 mmol/l, > 8 and 10 mmol/l, were analyzed using linear mixed models, during the final week of each arm, measured by blinded CGM (IPro2®). Results 31 children (15 females) finished the study. With sensor compliance > 60%, no difference in TIT was found, TIT: A 37.86%; 95% CI [33.21; 42.51]; B 37.20%; 95% CI [32.59; 41.82]; < 3 mmol/l A 2.27% 95% CI [0.71; 3.84] B 1.42% 95% CI [-0.13; 2.97]; > 8 mmol/l A 0.60% 95% CI [0.56, 0.67]; B 0.63% [0.56; 0.70]. One year after the study all participants were on CGM compared to 80.7 % prior to the study, with a shift of 13/25 participants from iscCGM to SAP. Conclusions In this study, no significant difference in glycemic control was found whether treated with SAP (SmartGuard®) or pump with iscCGM. The decision of all families to continue with CGM after the study suggests a positive impact, with preference for SmartGuard®.